Characterization of the complete mitochondrial genome of Bothrocara hollandi (Perciformes: Zoarcidae) - Nack-Keun Kim; Sapto Andriyono; Jobaidul Alam; Sung-Tae Kim; Kyung Mi Jung; Hyun-Woo Kim (Mitochondrial DNA. Part B. Resources, 2019)
The full mitogenome of Bothrocara hollandi was determined by high-throughput sequencing (HTS) platform. The genome was 16,732 bp in length, which included 13 protein-coding genes, 22 tRNAs, two ribosomal RNAs (12S and 16S), and a control region (D-Loop). The overall composition of G + C in the mitogenome was 45.90%, which was lower than A + T contents (54.10%). Except for COX1 (GTG), the other twelve protein-coding genes begin with typical start codon, ATG. The incomplete stop codon (TA − or T–) was identified in five genes, including COXI, COXII, COXIII, ND3, and ND4. The phylogenetic analysis with the currently reported mitogenome sequences showed that B. hollandi was most closely related to Lycodes tanakae, suggesting that additional mitogenome sequences in genus Bothrocara are required for its clear evolutional relationship.